2011
DOI: 10.1002/art.30591
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor promoter polymorphism TNF*-857 is a risk allele for psoriatic arthritis independent of the PSORS1 locus

Abstract: Objective. The strongest susceptibility locus of psoriatic arthritis (PsA) is within the major histocompatibility complex (MHC) region (psoriasis susceptibility region 1, or PSORS1), and HLA-Cw*06:02 has been reported as the PSORS1 susceptibility allele. Non-HLA genes within the MHC region have also been implicated in PsA, but because of the strong linkage disequilibrium at chromosome 6p21, it is difficult to make a distinction between susceptibility alleles and linked markers. Recent studies have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
3
15
0
2
Order By: Relevance
“…A previous study has pointed out that the serum TNF-α level was increased in the -1031 T/C genotype carriers, and TNF-α polymorphism correlated with TNF-α level in patients with acute coronary syndrome. 32 Giardina et al 33 also demonstrated that TNF-α -857C/T might act as an independent risk factor for psoriatic arthritis, which is consistent with our study. Furthermore, from the study we observed that the patients with ocular MG showed lower frequencies of the TT genotype and the T allele of TNF-α -857C/ T than those with generalized MG. Ocular MG, prior to generalized MG stage, is an initial form of MG that accounts for~50% of all MG; although there has been a declined rate of ocular MG progressing to generalized MG in MG patients owing to the development of immuomodulation therapies including prednisone therapy, the disease progression is still inevitable.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study has pointed out that the serum TNF-α level was increased in the -1031 T/C genotype carriers, and TNF-α polymorphism correlated with TNF-α level in patients with acute coronary syndrome. 32 Giardina et al 33 also demonstrated that TNF-α -857C/T might act as an independent risk factor for psoriatic arthritis, which is consistent with our study. Furthermore, from the study we observed that the patients with ocular MG showed lower frequencies of the TT genotype and the T allele of TNF-α -857C/ T than those with generalized MG. Ocular MG, prior to generalized MG stage, is an initial form of MG that accounts for~50% of all MG; although there has been a declined rate of ocular MG progressing to generalized MG in MG patients owing to the development of immuomodulation therapies including prednisone therapy, the disease progression is still inevitable.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed the author suggests that this polymorphism is associated with higher TNF- α production [32]. Studies in adult patients have recently demonstrated that −857T allele is an independent risk allele for psoriatic arthritis [79, 80] but similar data were not founded in children. Zeggini et al examined the association of multiple TNF SNPs (−1031, −863, −857, −376, +489A, +851, +1304) with juvenile oligoarthritis by constructing and analyzing SNP-tagged TNF haplotype in 144 simplex families consisting of parents and affected children.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the environmental risk factors, it is important to mention: stress, low-humidity, drugs, smoking, obesity and chronic infections. In addition, numerous susceptibility genes and variants (LCE3B, LCE3C, TRAF3IP2, polymorphisms in IL-17, IL-23, RUNX3 and TNF*-857) have been recognized as contributing risk factors for PsA [15,[18][19][20][21][22][23][24]. Concerning the treatment of PsA, the available therapeutic approaches are mainly oriented to relief the inflammation and/or the associated-symptoms and to 'slow-down' the progression to more advanced and severe stages of the disease.…”
Section: Pharmacogenomics and Psoriatic Arthritismentioning
confidence: 98%